Wealth optimization: A conceptual model of financial literacy, financial socialization, parental norms and money attitude - D. Sundarasen, Sheela Devi; Rahman, Muhammad Sabbir; Othman, Noor Shahaliza; Danaraj, Jennifer (American Scientific Publishers, 2016)
This study has incorporated an integrated conceptual model which investigates the impact of financial literacy, financial socializations, parental norms and attitude towards money on wealth optimization. Wealth optimization includes budgeting, spending, saving, and investing. The conceptual model is designed post a rigorous review of relevant literature. Empirical testing of the model is proposed and it is envisioned that the results of the study would increase the awareness amongst all stakeholders, i.e., the young adults, parents, and socialization agents on their role in wealth maximization plans. Additionally, the importance of financial literacy and an individual’s attitude towards money on wealth optimization is also highlighted in this study. The idea is novel and it is intended to make significant contribution to the stream of financial planning and wealth optimization research in a developing country.